(untitled) (CIPEEX, 2022)
ACCORDING TO STATISTICAL DATA FROM THE INSTITUTO PRÓ-LIVRO (IPL) ITA CULTURAL AND IBOPEINTELIGNCIA, SHOWN IN THEIR 5TH EDITION OF THE PORTRAITS OF READING IN BRAZIL (2019) SURVEY,THERE ARE APPROXIMATELY 100 MILLION READERS, WHICH MAKES UP 52% OF THE POPULATION, 4%LESS THAN IN THEIR PREVIOUS ANALYSIS (2015). IN THIS SCENARIO, IT WAS OBSERVED THAT THETECHNOLOGICAL ADVANCE HAS NOT TENDED SO MUCH TO THE USE OF THE GREATEST FRUIT OF MODERNITY,THE INTERNET, WHICH IN THIS PERIOD OF PANDEMIC CORONAVIRUS, HAS BECOME VITAL FOR BRAZILIANS,WHO HAD TO ADAPT THEIR DAILY LIVES TO A NEW LIFESTYLE. THUS, THIS ARTICLE AIMS TO DEVELOP ANAPPLICATION FOR EXCHANGING AND SELLING BOOKS IN ORDER TO BE THE SOLUTION FOR A GROUP OF PEOPLEWHO ARE AND WANT TO BE READERS, NAMED AS TROKATROKA , USING METHODOLOGIES ANDTECHNIQUES RELATED TO WEB AND MOBILE DEVELOPMENT SUCH AS C#,GO LANG, REACT, REACTNATIVE, JAVASCRIP, JAVA,ALL OF THEM FOR COMPUTER AND CELL PHONE ON WINDOWS AND ANDROIDOPERATING SYSTEMS RESPECTIVELY, SWIFT, FOR IOS DEVICES AND LAST BUT NOT LEAST MONGODB ANDSQLSERVER FOR OUR DATABASE MANAGEMENT.AND ABOUT THE METHODOLOGIES, AND ABOUT THEMETHODOLOGIES, WE USE THE WHOLE BASIS OF A SOLID DEVELOPMENT OF THE SIZE WE ARE PROPOSING,USING FOR THIS PURPOSE TECHNIQUES RELATED TO ENGINEERING LIFECYCLE MANAGEMENT, PROJECTPLANNING, DESIGN AND USER EXPERIENCE PLANNING , ARCHITECTURAL PLANNING, CONTINUOUSINTEGRATION PLANNING, VERIFICATION AND VALIDATION. THAT WAY, WE AIM TO MAKE POSSIBLE,FACILITATE AND ENCOURAGE A PRACTICE THAT HAS BEEN LONG LEFT ASIDE, AND ALSO TO MODIFY A MARKET MODEL, WHICH INCREASINGLY SEES THE NEED TO ADAPT TO THE NEW DEMANDS OFTHE MARKET AND ITS USERS.